PENGARUH SISTEM ZONASI TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS VII DI SMP NEGERI 9 PALU - Sabri, Triani Wahyuni; Listiqowati, Ika; Putra, Exsa (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
This research aims to analyze the effect of the zoning system on students' learning achievement at class VII SMPN 9 Palu. This research used a descriptive method with a quantitative approach. The population in this research was all students at class VII SMPN 9 Palu, totaling 231 students, and 25% or 57 of them would be taken as samples. Data were collected through observation, interviews, questionnaires, and documentation techniques. The research instrument was tested with validity and reliability tests. Data analysis used percentage descriptive statistics, correlation statistics, chi-square statistics, linearity test statistics, and homogeneity tests. This research proves the zoning system's positive and significant effect on the students' learning achievement at class VII SMPN 9 Palu. The calculation of student achievement in the conversion table found the average value of student learning achievement of 56.86, which is in the medium category. The results of the analysis calculation on the normality test using chi-squared statistics obtained chi-squared count = 13.97 with chi-squared table = 11.070, then chi-squared count < chi-squared table. The analysis results on the linearity test using the Fobs statistic were obtained = 0.596 with Ftable = 5.05 then Fobs ≤ Ftable..The analysis results on the homogeneity test X2obs = 0.347 with X2 table = 3.841 then X2obs ≤ X2table. The t-test obtained tcount = 12.681 with ttable = 0.632. Because of the value of tcount > ttable, it can be concluded that the correlation is significant or the working hypothesis (Ha) is accepted.